2017
DOI: 10.1038/srep43782
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fibroblast growth factor 21 (FGF21) in obese, insulin resistant states is normalised by the synthetic retinoid Fenretinide in mice

Abstract: Fibroblast growth factor 21 (FGF21) has emerged as an important beneficial regulator of glucose and lipid homeostasis but its levels are also abnormally increased in insulin-resistant states in rodents and humans. The synthetic retinoid Fenretinide inhibits obesity and improves glucose homeostasis in mice and has pleotropic effects on cellular pathways. To identify Fenretinide target genes, we performed unbiased RNA-seq analysis in liver from mice fed high-fat diet ± Fenretinide. Strikingly, Fgf21 was the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…Serum FGF21 levels in patients with fatty liver and WD-fed mice were also studied as increased serum FGF21 level is a potential biomarker for metabolic disorders. 34,35 Consistent with published findings, elevated serum FGF21 levels were found in both human patients and obese mice with fatty livers ( Fig. 1A and C).…”
Section: Mir-22supporting
confidence: 91%
“…Serum FGF21 levels in patients with fatty liver and WD-fed mice were also studied as increased serum FGF21 level is a potential biomarker for metabolic disorders. 34,35 Consistent with published findings, elevated serum FGF21 levels were found in both human patients and obese mice with fatty livers ( Fig. 1A and C).…”
Section: Mir-22supporting
confidence: 91%
“…Several lines of evidence indicate that the metabolic hormone, FGF21, plays a key role in obesity-associated metabolic syndrome 34 . Indeed, increased plasmatic levels of FGF21 have been found in HFD mice 35 and metabolically unhealthy obese patients 34 . Since FGF21 can be induced in BAT by PPARγ agonists 36 , we were interested to explore whether or not VCE-004.8 had some role on FGF21 in different tissues and cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the above stimulatory responses may contribute to the improved glycemic profile of lean mice treated with VCE-004.8. Intriguingly, while fasting is known to potently enhance FGF21 levels, as major mechanisms to coordinate adaptive responses to starvation 50 , obesity has been shown to cause also an enhancement of FGF21 levels in rodents and humans 34 , 35 , suggesting a state of “FGF21 resistance”, defined by elevated FGF21 levels and impaired FGF21 receptor function 51 , which might contribute to the aggravation of metabolic state in conditions of obesity. In good agreement, in our studies, HFD caused an elevation of FGF21 levels, associated to increased FGF21 mRNA expression in liver and WAT, while VCE-004.8 administration normalized serum FGF21 concentrations and iWAT FGF21 gene expression; the latter is compatible with an alleviation of the state of FGF21 resistance linked to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 is expressed in the liver and plays an important role in regulating lipid and glucose metabolism. Several studies have shown that FGF21 overexpression in rodents is associated with weight loss and lower obesity, as well as insulin sensitivity in its target tissues 20 , 28 , 29 . However, the metabolic role of FGF21 in humans is not completely clear.…”
Section: Discussionmentioning
confidence: 99%